Occupational coping self-efficacy explains distress and well-being in nurses beyond psychosocial job characteristics - Pisanti, Renato; van der Doef, Margot; Maes, Stan; Lombardo, Caterina; Lazzari, David; Violani, Cristiano (Frontiers in Psychology, 2015)
Aims: The main purpose of the present study was to extend the Job Demand Control Support (JDCS) model analyzing the direct and interactive role of occupational coping self-efficacy (OCSE) beliefs. Background: OCSE concern an individual's beliefs about one's ability to cope with occupational stressors. The interplay between occupational stressors, job resources and self-efficacy beliefs is poorly investigated. The present research attempts to address this gap. Design: Cross-sectional survey. Method: Questionnaire data from 1479 nurses (65% response) were analyzed. Hierarchical regression analyses were used to test the direct and moderating role of OCSE in conjunction with job demands (i.e., time pressure), and two job resources: job control (i.e., decision latitude and skill discretion) and social support (i.e., supervisor support and coworker support) in predicting psychological distress and well-being. Results: Our findings indicated that high demands, low job control and low social support additively predicted the distress/well-being outcomes (job satisfaction, emotional exhaustion, depersonalization, psychological distress, and somatic complaints). Beyond the main effects, no significant interactive effects of demands, control, and support were found. Occupational coping self-efficacy (OCSE) accounted for an additional 1% to 4% of the variance in the outcomes, after controlling for the JDCS variables. In addition, the results indicate that occupational coping self-efficacy buffers the association between low job control and the distress dimensions emotional exhaustion, depersonalization, and psychological distress. Low control was detrimental only for nurses with low occupational coping self-efficacy. Conclusion: Our results suggest expanding the JDCS model incorporating individual characteristics such as occupational coping self-efficacy beliefs, for predicting psychological distress and well-being. Limitations of the study and practical implications are discu